Maximizing public service through a humanistic communication approach - Ainal Fitri; Asmaul Husna; Yuhdi Fahrimal; Futri Syam (Community Empowerment, 2024)
Optimal public service by an institution is closely tied to effective communication practices. However, at the West Aceh Police, the desire to maximize public services is impeded by communication problems between police officers and the public during service provision. This issue has prompted community service activities aimed at enhancing public services by improving communication skills, particularly through a humanistic approach. The training involved 30 members of the West Aceh Police and utilized various methods such as lectures, discussions, basic communication techniques training, and public speaking exercises. The objective was to identify communication shortcomings in service provision, evaluate them based on participants' experiences, and rectify them to enhance performance. Results revealed that participants frequently encountered communication failures with the public and had yet to fully implement a humanistic communication approach. However, the training significantly improved participants' ability to analyze and reflect on communication failures, empowering them to devise their own solutions.